2013
DOI: 10.1182/blood-2012-10-461491
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant 3′ oligoadenylation of spliceosomal U6 small nuclear RNA in poikiloderma with neutropenia

Abstract: Key Points• Crystal structure of human USB1 identifies it as a member of the LigT-like superfamily of 2H phosphoesterases.• USB1 protects spliceosomal U6 small nuclear RNA from aberrant 3Ј oligoadenylation.The recessive disorder poikiloderma with neutropenia (PN) is caused by mutations in the C16orf57 gene that encodes the highly conserved USB1 protein.Here, we present the 1.1 Å resolution crystal structure of human USB1, defining it as a member of the LigT-like superfamily of 2H phosphoesterases. We show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
125
4
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(144 citation statements)
references
References 47 publications
12
125
4
3
Order By: Relevance
“…21 By contrast, USB1 deletion in yeast cells showed lower levels of cellular U6, leading to general pre-mRNA splicing defects. 19 To investigate the effects of usb1 knockdown on the pre-mRNA splicing in zebrafish, we examined the total RNA by sqRT-PCR and analyzed the expression of the genes involving the differentiation and development of neutrophils.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…21 By contrast, USB1 deletion in yeast cells showed lower levels of cellular U6, leading to general pre-mRNA splicing defects. 19 To investigate the effects of usb1 knockdown on the pre-mRNA splicing in zebrafish, we examined the total RNA by sqRT-PCR and analyzed the expression of the genes involving the differentiation and development of neutrophils.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the loss of USB1 activity, the steady state levels of U6 snRNA were unaffected in PN patients. 21 This might be attributed to the presence of multiple and dispersed U6 snRNA genes that have varied transcriptional efficiencies in humans. 40 Although we have not determined the 3 0 end sequence of U6 snRNA in this study, instead we observed that the expression of U6 snRNA was not altered by the usb1 knockdown in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations